Reopening the dialogue between the theory of social representations and discursive psychology for examining the construction and transformation of meaning in discourse and communication - Batel, S.; Castro, P. (British Journal of Social Psychology, 2018)
The theory of social representations (TSR) and discursive psychology (DP) originated as different social psychological approaches and have at times been presented as incompatible. However, along the years convergence has also been acknowledged, and, lately, most of all, practised. With this paper, we discuss how versions of TSR focusing on self–other relations for examining cultural meaning systems in/through communication, and versions of DP focusing on discourse at cultural, ideological, and interactional levels, can come together. The goal is to help forge a stronger social–psychological exploration of how meaning is constructed and transformed in and through language, discourse, and communication, thus extending current understanding of social change. After presenting a theoretical proposal for integrating those versions of TSR and DP, we offer also an integrated analytical strategy. We suggest that together these proposals can, on one hand, help TSR systematize analyses of social change that are both more critical and better grounded in theorizations of language use, and, on the other, provide DP with analytical tools able to better examine both the relational contexts where the construction and transformation of meaning are performed and their effects on discourse. Finally, we give some illustrations of the use of this analytical strategy.